Efektivitas Media Guessing Word Dalam Meningkatkan Penguasaan Kosakata Bahasa Arab Siswa Kelas X SMA Muhammadiyah 1 Tangerang - Husna, Asmaul; Abidin, Zainul (Shaut al Arabiyyah, 2024)
Vocabulary mastery in Arabic language learning, especially at SMA Muhammadiyah 1 Tangerang, is very important. Currently, the Arabic language teaching method at the school is still conventional and less engaging, resulting in students being less enthusiastic and experiencing difficulties in memorizing vocabulary. This study aims to test the effectiveness of the "guessing word" strategy in improving the vocabulary mastery of Arabic language students in grade X at SMA Muhammadiyah 1 Tangerang. The research method used was an experiment with a One Group Pretest-Posttest Design, involving 32 students in grade X as samples. The results showed a significant improvement in vocabulary mastery after implementing the "guessing word" strategy. The average student score in the pretest was 65.3, while in the posttest it increased to 87.9. Thus, the "guessing word" strategy has been proven effective in improving the vocabulary mastery of Arabic language students at SMA Muhammadiyah 1 Tangerang.